DNA rearrangement on the octadecylamine modified graphite surface by heating and ultrasonic treatment. (11th November 2020) - Xiong, Xiaolu; Han, Junfeng; Chen, Yu; Li, Shanshan; Xiao, Wende; Shi, Qingfan
Abstract: The evolution of single-stranded DNA (ssDNA) assembly on octadecylamine (ODA) modified highly oriented pyrolytic graphite (HOPG) surface by heating and ultrasonic treatment has been studied for the first time. We have observed that DNA on the ODA coated HOPG surface underwent dramatic morphological changes as a function of heating and ultrasonic treatment. Ordered DNA firstly changed to random aggregates by heating and then changed to three-dimensional (3D) networks by ultrasonic treatment. This finding points to previously unknown factors that impact graphite–DNA interaction and opens new opportunities to control the deposition of DNA onto graphitic substrates. In this way, we built a cost-effective method to produce large-scale 3D ssDNA networks. All of these studies pave the way to understand the properties of DNA–solid interface, design novel nanomaterials, and improve the sensitivity of DNA biosensors.